Proceedings of the Genetic and Evolutionary Computation Conference 2019
DOI: 10.1145/3321707.3321817
|View full text |Cite
|
Sign up to set email alerts
|

Deep neuroevolution of recurrent and discrete world models

Abstract: Neural architectures inspired by our own human cognitive system, such as the recently introduced world models, have been shown to outperform traditional deep reinforcement learning (RL) methods in a variety of different domains. Instead of the relatively simple architectures employed in most RL experiments, world models rely on multiple different neural components that are responsible for visual information processing, memory, and decision-making. However, so far the components of these models have to be train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Gaming similarly to DRL, gaming represents one of the main testbeds for ES. Most of the literature on ES reviewed in this survey test their algorithms on Atari games [4,5,29,32,256,257,258,259]. These are considered to be challenging as they present the agents with high dimensional visual inputs and a diverse and interesting set of tasks that were designed to be difficult for humans players [14].…”
Section: B Evolution Strategy Applicationsmentioning
confidence: 99%
“…Gaming similarly to DRL, gaming represents one of the main testbeds for ES. Most of the literature on ES reviewed in this survey test their algorithms on Atari games [4,5,29,32,256,257,258,259]. These are considered to be challenging as they present the agents with high dimensional visual inputs and a diverse and interesting set of tasks that were designed to be difficult for humans players [14].…”
Section: B Evolution Strategy Applicationsmentioning
confidence: 99%
“…similarly to DRL, gaming represents one of the main testbeds for ESs. Most of the literature on ESs reviewed in this survey test their algorithms on Atari games [4,5,29,32,226,227,228,229]. These are considered to be challenging as they present the agents with high dimensional visual inputs and a diverse and interesting set of tasks that were designed to be difficult for humans players [14].…”
Section: B Evolution Strategy Applicationsmentioning
confidence: 99%
“…Interestingly, this approach also allowed an agent to get better by training inside a hallucinated environment created through a trained world model. Instead of first training a policy on random rollouts, follow-up work showed that end-to-end learning through reinforcement learning [28] and evolution [65,66] is also possible. We will discuss MuZero as another example of planning in latent space in Section 6.…”
Section: Learning To Play From Pixelsmentioning
confidence: 99%